The Duration of Sodium Methoxide Catalyst Impregnation in Methanol and Its Impact on the Reduction Monoglyceride Content in Biodiesel Production - Sinaga, Boy Andika; Darma, Frandika; Rahmadhani, Rahmadhani (Journal of Engineering and Science Application, 2025)
Biodiesel is one of the most promising alternatives to replace conventional fuel products, specifically diesel. The increasing use of biodiesel is currently a focus of many researchers aiming to improve its quality, one of which involves reducing the monoglyceride content. High monoglyceride content can cumulatively affect the performance of diesel engines. Several techniques are used to reduce the monoglyceride content in biodiesel, one of which is maximizing the transesterification reaction. This study focuses on the preparation stage before the transesterification reaction, where the treatment involves variations in the impregnation of sodium methoxide (NaOCH3) in methanol (CH3OH). The impregnation durations tested were 0, 10, 20, 30, and 40 minutes during chemical mixing. The transesterification process was then carried out at reaction temperatures of 62°C and 64°C. The results indicate that the duration of impregnation between sodium methoxide (NaOCH3) and methanol (CH3OH) affects the reduction of the monoglyceride content. The optimal condition identified in this study was an impregnation duration of 20 minutes at a reaction temperature of 62°C, which resulted in a monoglyceride content of 0.3629%.